Information Technology Reference
In-Depth Information
4
A Special Realization Algorithm
In Algorithm 2.1, if m = 1 there is a unique vector ( a 1 ,
···
,a n ) in reduction
step such that j =1 a j θ ( ω j )= 0 n . However in general there are many choices
about the vector ( a 1 ,
,a n ) and so we give a special choice such that the total
number of reduction steps is as small as possible.
First we introduce length parameters, that is, N i = v ( η ( ω i ))
···
v ( ω i )for1
i
n . Hence we have δ j ( η ( ω i ) ,T )= 0 p for j =1 ,...,N i
1, but δ N i ( η ( ω i ) ,T )
= 0 p .Inparticular, N i = N +1 if and only if θ ( ω i )
= 0 m . According to these
parameters, combine certain reduction steps into a small while-loop and let r
denote the current number of such small while-loops. It will be showed that at
each r , the recursively updated basis ω 1 ,...,ω n satisfies the following conditions.
1. θ ( ω 1 ) ,...,θ ( ω p ) are linearly independent over IF and θ ( ω j )= 0 m for j =
1 ,...,p .
2. θ ( η ( ω p +1 )) ,...,θ ( η ( ω p + m )) are linearly independent over IF.
3. For each s , p +1
s
n , N s >N j for j =1 ,...,p .
Put r
0 when the same initialization is given as Algorithm 2.1 and at this
time the above conditions are trivially satisfied.
In the above situation one proceeds as follows. If θ ( ω p + i ) = 0 m for i =
1 ,...,m , the basis becomes normal just by rearranging the order of the ba-
sis elements since the basis satisfies Condition 1, 2 and 3, and so let M N ( z )=
( η ( ω p + i )) 1 ≤i≤m and pol( T ( z ) M N ( z )) M N ( z )isan N th minimal partial realiza-
tion of T . Therefore the algorithm terminates.
Otherwise, set I =
{
p +1
s
n : θ ( ω s )= 0 m and N s is minimum
}
.
Choose a number s
I and do the following reduction step. Since θ ( ω s )= 0 m
and so there exists a unique vector ( a 1 ,...,a p ) such that θ ( ω s )= j =1 a j θ ( ω j ).
Let h be an integer such that v ( ω h )=max
{
v ( ω j ): 1
j
p, a i
=0
}
. We need
to consider two cases.
Case 1. Suppose v ( ω s )
v ( ω h ). In this case we let
p
a j z −v ( ω j )+ v ( ω s ) ω j .
ξ = ω s
(6)
j =1
j =1 a j z −v ( ω j )+ v ( ω s ) η ( ω j ). From (6) we have v ( ξ ) <
v ( ω s ). Then ω s is replaced by ξ and the other ω j are unchanged.
Case 2. Suppose v ( ω s ) <v ( ω h ). Then we let
Clearly, η ( ξ )= η ( ω s )
p
ξ = z −v ( ω s )+ v ( ω h ) ω s
a j z −v ( ω j )+ v ( ω h ) ω j .
(7)
j =1
j =1 a j z −v ( ω j )+ v ( ω h ) η ( ω j ). From
(7), we have v ( ξ ) <v ( ω h ). Then we replace ω h by ω s , ω s by ξ , and leave the
other ω j unchanged.
Similarly, we have η ( ξ )= z −v ( ω s )+ v ( ω h ) η ( ω s )
Search WWH ::




Custom Search